The effects of perineal trauma on immediate self-reported birth experience in first-time mothers. (3rd April 2022) - Molyneux, Rebecca; Fowler, Gillian; Slade, Pauline
Abstract: Introduction: Childbirth can sometimes be stressful or traumatic, and previous research has considered how birth complications and interventions may contribute to a negative birth experience. One of the most frequent complications during birth is trauma to the perineum. The aim of this study was to investigate whether different levels of perineal trauma were associated with differences in women's evaluation of their birth experience. Materials and methods: As part of a longitudinal cohort study, the self-reported birth experiences of 202 primiparous women were compared based on the degree of perineal trauma they had experienced. Women who had given birth for the first time, vaginally and within the last 48 h in a large tertiary maternity unit in England were invited to take part. Data were collected from their hospital records with their consent and using the Childbirth Experience Questionnaire (CEQ), Experience of Birth Scale (EBS) and a perineal pain Visual Analogue Scale (VAS). Results: Women with an obstetric anal sphincter injury (OASI) or episiotomy reported a more negative overall birth experience and perceived themselves as having less ability to give birth compared to those with a 1st/2nd degree sutured tear. Those with an episiotomy also reported feeling less involved in decision making processes during their birth. Significant differences remained between the OASI and 1st/2nd degree tear groups when controlling for factors known to affect birth experience, highlighting severe perineal trauma as a potential contributor to more negative birth experience. Conclusions: Perineal trauma may affect a woman's birth experience. Experiencing an episiotomy should not be overlooked as a potential contributor, especially during instrumental birth and in the absence of involved decision making. Further research is needed to disentangle the effects of episiotomy on birth experience, to explore the care needs of women with different degrees of perineal trauma and to explore how a negative birth experience may contribute to poor psychological health in the longer term.